(untitled) (The International Journal for Scientific Research, 2026)
Commercial mortgages are among the most prominent forms of tangible security upon which credit transactions are based, particularly in the modern business environment characterized by speed and the merchant’s reliance on financing. This research examines the regulatory framework of commercial mortgages in the Kingdom of Saudi Arabia and its complementary relationship with the system of securing rights in movable assets. It analyzes the nature of commercial mortgages, their essential elements, the conditions for their legal validity, and their legal effects on the contracting parties (the mortgagor, the mortgagee, and the notary), in addition to the mechanisms for enforcing the mortgaged asset and the circumstances under which the mortgage is extinguished. The research adopts a descriptive-analytical approach, focusing on recent regulatory texts (Royal Decree No. M/86 of the Commercial Mortgage Law and Royal Decree No. M/94 of the System of Securing Rights in Movable Assets) and their implementing regulations, while also drawing upon specialized jurisprudential and legal references. The research concludes that the Saudi legislator has successfully achieved a legislative balance that enhances the protection of the mortgagee by granting them priority and pursuit rights, and by permitting non-judicial enforcement with clear procedural controls, without compromising the guarantees of the mortgagor. The inclusion of commercial mortgages within the scope of the security of rights system has led to broader regulatory integration, but it has also resulted in some practical overlaps that require further clarification and refinement. The research concludes with a set of practical recommendations, most notably: developing electronic registration and publication platforms, enhancing regulatory awareness among traders in the commercial sector, and encouraging applied studies and comparisons with international models. This abstract aims to provide a concise and comprehensive reference for researchers and legal practitioners on commercial mortgage guarantees within the contemporary Saudi legal framework.